Study of the Excess Cost Associated with Drug Wastage Due to Limited Vial Size Options of the Intravenous Drugs for Anti-cancer Treatment, Among Patients Receiving Such Treatment at Tata Memorial Hospital - Tiwari, Atul; Kulkarni, Sheetal; Jadhav, Bhagyashree; Menon, Nandini; Prabhash, Kumar; Nonronha, Vanita; Madaan, Shafak; Bhosale, Snehal; Sagvekar, Chaitynaya; Nikam, Preeti; et al. (Asian Pacific Journal of Cancer Care, 2024)
Aims and Objectives: To evaluate the drug wastage and additional costs (in INR) resulting from leftover or unused drugs due to limited vial strength options, and to propose vial size recommendations to pharmaceutical companies tailored to Indian requirements. Material and Methods: A total of 500 adult patients attending daycare oncology were prospectively evaluated. Mean, median, mode and left over or unused drug dose for each chemotherapy drugs were calculated. The economic loss estimation was done considering the unit cost for the drug. Result: The overall drug wastage for 500 prescriptions was 57,836 mg, accounting for 8.67% of the total prescribed dose. This resulted in an economic loss of 1,02,562 INR, which is 6.26% of the total cost. The highest proportions of drug wastage were observed for vincristine (28.72%), etoposide (23.20%), bleomycin (18.5%), pemetrexed (17.10%), nab-paclitaxel (16.37%), vinblastine (14.70%), Adriamycin (11.76%), and carboplatin (11.36%). The maximum economic loss was attributed to carboplatin (19.66%), nab-paclitaxel (17%), etoposide (14.5%), oxaliplatin (9.45%), and pemetrexed (7%). In combination chemotherapy regimens, gemcitabine-cisplatin-nab-paclitaxel (18.52%), pemetrexed-carboplatin (11.82%), and carboplatin-etoposide (8.97%) were responsible for the highest monetary losses due to drug wastage. Conclusion: Drug wastage due to oversized chemotherapy vials imposes significant financial and environmental burdens. We recommend offering additional vial size options for carboplatin, etoposide, gemcitabine, nab-paclitaxel, irinotecan, vincristine, and 5-FU. We hope this will reduce drug wastage to below 1-2%.